Religiosity and Emotion Regulation: A Systematic Literature Review - Intan Mutiawati Firdaus; Rahma Zikra (al-Afkar, Journal For Islamic Studies, 2025)
Individuals who have a high level of religiosity tend to be calmer in living life because they are broader in looking at life's problems and more deeply in looking at life's goals. The high level of religiosity is related to a high level of emotional regulation because with high religiosity, individuals are more accepting of events in life so that their emotional regulation is also more organized. Objective: The purpose of this study was to group the results of various recent studies on religiosity and emotion regulation experienced by individuals broadly from elementary school to adulthood. Methods: The method used in this study is systematic literature research (SLR).  Results: On an initial search, researchers found 297 journals. After further review, there were 28 journals that met the criteria and were relevant to the research objectives. Conclusion: Religiosity is an individual's self-value as the basis for responsibility for his actions to himself, others, and God. In high religiosity, a high level of emotion regulation is also found. In addition, individuals who have high religiosity tend to have psychological well-being and are easier to seek psychological help if they encounter difficulties in life.